2016
DOI: 10.1038/onc.2015.511
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cholesterol metabolism underlies synergy between mTOR pathway inhibition and chloroquine in bladder cancer cells

Abstract: Mutations to fibroblast growth factor receptor 3 (FGFR3) and phosphatase and tensin homologue (PTEN) signalling pathway components (for example, PTEN loss, PIK3CA, AKT1, TSC1/2) are common in bladder cancer, yet small-molecule inhibitors of these nodes (FGFR/PTENi) show only modest activity in preclinical models. As activation of autophagy is proposed to promote survival under FGFR/PTENi, we have investigated this relationship in a panel of 18 genetically diverse bladder cell lines. We found that autophagy inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 56 publications
5
44
0
Order By: Relevance
“…5B). This is also in agreement with other publications suggesting an overlap in the FGFR and PI3K/ AKT pathways (3,6,21,37,38).…”
Section: Discussionsupporting
confidence: 82%
“…5B). This is also in agreement with other publications suggesting an overlap in the FGFR and PI3K/ AKT pathways (3,6,21,37,38).…”
Section: Discussionsupporting
confidence: 82%
“…Upregulation of autophagy promotes tumorigenesis and tumor aggressiveness [28, 29]. CQ is among several autophagy inhibitors that have been tested in combination with other anticancer drugs [18, 19, 24, 30, 31]. Although the mechanism of action is still not fully understood, CQ is believed to inhibit autophagy in cancer cells by preventing the fusion of autophagosomes and lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Although CQ and HCQ were initially tested in cancer treatment due to their ability to inhibit autophagy, we now know that their therapeutic effect depends on other mechanisms as well [2123]. For example, a recent report revealed that CQ-induced cancer cell death was related to its inhibitory effects on cholesterol metabolism [24]. Taking advantage of its recently uncovered CXCR4 antagonism, CQ was able to inhibit CXCR4/CXCL12-mediated pancreatic cancer cell invasion and proliferation in vitro, to eliminate established tumors, and to improve overall survival when combined with gemcitabine in vivo [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since our in vitro cytotoxicity studies demonstrated that CMQ outperforms traditional quinolones at killing cancer cells, we sought to determine whether CMQ shared a similar mechanism of action with CQ and HCQ. CQ and HCQ accumulate in lysosomal compartments and disrupt lysosomal functions, including lysosome‐associated autophagy, although these compounds may also be inhibiting other cellular processes that are dependent upon lysosomal integrity . To determine whether differences between CMQ and CQ cytotoxic activity were due to biovailability and subsequent accumulation of these compounds in various cellular compartments, we used a cell fractionation approach coupled with high sensitivity measurement of drug analytes by HPLC‐MS/MS.…”
Section: Resultsmentioning
confidence: 99%